VD_FINDINFO Jug / 2016 / 153 vom 21. Oktober 2015 - VD Tribunal cantonal (2015)
ESCROQUERIE, FIXATION DE LA PEINE, SURSIS À L'EXÉCUTION DE LA PEINE | 137 ch. 2 CP, 138 ch. 1 CP, 139 ch. 1 CP, 146 al. 1 CP, 149 CP, 150 CP, 172ter CP, 251 ch. 1 CP, 252 CP, 90 ch. 2 LCR, 19a ch. 1 LStup